The Role of Village Government in Addressing Cultural Conflicts in Fadoro Fulolo Village, Lotu District, North Nias Regency: - Zebua, Fransiska Septania; Ndraha, Ayler Beniah; Lahagu, Palindungan; Telaumbanua, Eliagus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The research aims to explore the formulation of the issues mentioned above. To achieve this goal, data collection techniques such as interviews, observations, and documentation were employed, targeting both village officials and community members of Fadoro Fulolo Village. This thesis adopts a qualitative research approach, utilizing interviews as the primary method of data analysis to ensure the accuracy of the obtained data. The findings of this study reveal the efforts of the Village Government in addressing cultural conflicts in Fadoro Fulolo Village, Lotu District, North Nias Regency, as follows: Improving and enhancing the quality of management within the Fadoro Fulolo Village Government. Empowering the community. Collaborating with external parties to assist in resolving cultural conflicts or other conflicts that occur in Fadoro Fulolo Village. The Bhabinkamtimbmas (Police Officers as Community Security and Order Facilitators) conduct house-to-house visits, assist in problem-solving or conflict resolution, take action in criminal conflicts, provide temporary protection to the community, and offer guidance to the community or village government regarding issues related to security and police services. Additionally, the Babinsa (Non-Commissioned Officers as Village Developers) play a role in addressing cultural conflicts by Ensuring equal and fair service distribution to the community.